2013
DOI: 10.1271/bbb.120787
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analyses of a Strong Chitin-Binding Protein-1 (SCBP-1) from the Exoskeleton of the Crayfish <i>Procambarus clarkii</i>

Abstract: The organic matrices in the exoskeleton of the crayfish Procambarus clarkii are classified into three groups depending on solubility; acid soluble, acid insoluble-SDS/dithiothreitol (DTT) soluble, and acid insoluble-SDS/DTT insoluble fractions. In our previous studies, Casp-1 and -2 were identified in the acid soluble fraction, and CAP-1 and -2 were identified in the acid insoluble-SDS/DTT soluble fraction. In this study, acid insoluble-SDS/DTT insoluble materials were digested with proteases and the resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The newly identified Cq-M15 was found to share significant similarity with known proteins from arthropod cuticles and its sequence was more closely related to crustacean proteins from mineralized parts of the cuticle (Gosline, 1980;Inoue et al, 2008;Suzuki et al, 2013) and more distantly related to proteins found in crustacean non-mineralized arthrodial membranes (Gosline, 1980) and insect cuticles (Kim et al, 2005;Futahashi and Fujiwara, 2008;Werren et al, 2010). Such close homology further supports the involvement of Cq-M15 in biomineralization in the crayfish.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The newly identified Cq-M15 was found to share significant similarity with known proteins from arthropod cuticles and its sequence was more closely related to crustacean proteins from mineralized parts of the cuticle (Gosline, 1980;Inoue et al, 2008;Suzuki et al, 2013) and more distantly related to proteins found in crustacean non-mineralized arthrodial membranes (Gosline, 1980) and insect cuticles (Kim et al, 2005;Futahashi and Fujiwara, 2008;Werren et al, 2010). Such close homology further supports the involvement of Cq-M15 in biomineralization in the crayfish.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, several crustacean proteins associated with calcification processes present amino acid composition profiles similar to that of Cq-M15 (Inoue et al, 2004;Glazer et al, 2010). In fact, such shared patterns of amino acid composition were also found in proteins from organic matrices involved in invertebrate calcium carbonate precipitation (Faircloth and Shafer, 2007;Gayathri et al, 2007;Marie et al, 2007;Inoue et al, 2008;Suzuki et al, 2013), as well as in protein extracted from vertebrate enamel (Robinson et al, 2005).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The fibers of the exoskeletons of crustaceans contain chitin and matrix proteins that have a Rebers–Riddiford (RR) chitin‐binding concensus motif [23]. CAP‐1, CAP‐2, Casp‐2 and SCBP‐1 have the RR consensus motif and were identified from the exoskeleton of the crayfish [24–27]. The aromatic amino acids in the β‐sheet structure of the RR consensus motif bind to chitin through hydrophobic interactions [28].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a matrix protein that binds very strongly to chitin and cannot be extracted with a detergent solution, was identified. 41) As to the binding manner of this protein, there remains a possibility of covalent binding.…”
Section: Roles Of Organic Matrices In Biomineralizationmentioning
confidence: 99%